Prenatal CFAP53-related laterality defect: case report and review of the literature. (31st December 2023) - Mastromoro, Gioia; Guadagnolo, Daniele; Novelli, Antonio; Torres, Barbara; Piane, Maria; Magliozzi, Monia; Bernardini, Laura; Ventriglia, Flavia; Pizzuti, Antonio; Petrucci, Simona
Abstract: Laterality defects include morphological anomalies with impaired left-right asymmetry induction, such as dextrocardia, situs inversus abdominis, situs inversus totalis and situs ambiguus. The different arrangement of major organs is called heterotaxy. We describe for the first time a fetus with situs viscerum inversus and azygos continuation of the inferior vena cava, due to previously unreported variants in compound heterozygosity in the CFAP53 gene, whose product is implied in cilial motility. Prenatal trio exome sequencing was performed with turn-around time during the pregnancy. The fetuses with laterality defects are suitable candidates for prenatal exome sequencing due to the emerging high diagnostic rate of this group of morphological anomalies. A timely molecular diagnosis plays a fundamental role in genetic counseling, regarding couple decisions on the ongoing pregnancy, providing recurrence risks, and in predicting possible respiratory complications due to ciliary dyskinesia.